Aspects of the European Neighborhood Policy – Expression of the EU Global Policy (Economic and Political Thought, 2011)
The article is a part of broader research on the European NeighbourhoodPolicy and an attempt to answer a question about its significance and dimensionin the Common Foreign and Security Policy and the Common Foreignand Defence Policy. The main theme of the article is an analysis of the thesisthat the ENP is a sign of the existence of the Union’s global policy, anda comparison with a statement that it is nothing else than actions towards thecountries neighboring the European Union undertaken on an ad hoc basis inorder to enlarge the European security zone.